PENGUATAN PERAN MAHASISWA KKN DALAM MENDUKUNG SDGs DESA MELALUI EDUKASI PENGOLAHAN LIMBAH - Dati Nawastuti (LPPM Institut Pendidikan Nusantara Global, 2026)
Organic waste management in villages still faces various problems, including low awareness and technical skills in utilizing waste as a valuable resource. This condition has the potential to hamper the implementation of the Village Sustainable Development Goals (SDGs), especially in the sector of environmental sustainability and strengthening the local economy. This community service activity is focused on increasing the capacity of Community Service Program (KKN) students in managing organic waste based on compost and liquid organic fertilizer (POC) as a strategy to support sustainable village development. The program implementation method integrates participatory, educational, and practice-based approaches that are carried out in stages through socialization, training, direct practice in making compost, POC, and local microorganisms (MOL), and achievement measurements are carried out through a comparison of pre-test and post-test scores. The findings show an increase in student understanding of 41.67%, with an N-Gain value of 0.42 which is included in the medium effectiveness category. This increase indicates that the hands-on practice-based approach is effective in strengthening students' cognitive and technical capacity as agents of change in the village. This program not only improves student competency but also has the potential to become a replicable KKN provision model in supporting the implementation of Village SDGs through sustainable organic waste management.